Propranolol in hypertension: a dose-response study. Issue 6028 (17th July 1976) - Galloway, D B; Glover, S C; Hendry, W G; Logie, A W; Petrie, J C; Smith, M C; Lewis, J A; Simpson, W T
Abstract : The effect of propranolol was studied in a double-blind crossover trial in 24 carefully selected hypertensive outpatients. Each patient received propranolol 60 mg/day, 120 mg/day, 240 mg/day, and placebo for four weeks each according to a randomised sequence. Propranolol 60 mg/day was no better than placebo in reducing blood pressure. The effects of propranolol 120 mg/day and 240 mg/day were not significantly different. Both doses reduced lying blood pressure by about 20/10 mm Hg from an initial level of 173/104 mm Hg. No difference was detected between the effects of the different doses of propranolol and placebo on weight or on the occurrence of adverse reactions.